(-6)º + (-3)² + (-2)³ =
Soluções para a tarefa
Respondido por
2
Resposta:
. 2
Explicação passo-a-passo:
.
. (- 6)º + (- 3)² + (- 2)^3 =
. 1 + (- 3) . (- 3) + (- 2) . (- 2) . (- 2) =
. 1 + 9 + (+ 4) . (- 2) =
. 10 + (- 8) =
. 10 - 8
. 2
.
(Espero ter colaborado)
Eoueoeueoe:
Olá, Pfv Responde Minha Pergunta, Ela está Valendo 27 pontos,Pfv me ajude
Perguntas interessantes
Português,
8 meses atrás
Ed. Física,
8 meses atrás
Matemática,
8 meses atrás
Inglês,
9 meses atrás
Física,
1 ano atrás
Física,
1 ano atrás
Geografia,
1 ano atrás